Inovasi Snack Bar Dengan Proporsi Tepung Ubi Kayu (Manihot Esculenta) dan Tepung Kacang Hijau (Vigna Radiata) - Vanessa Melia Octaviany; Lilis Sulandari; Ita Fatkhur Romadhoni; Nugrahani Astuti (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to develop a snack bar innovation using a combination of cassava flour and mung bean flour in three different proportions: 35g:15g, 30g:20g, and 25g:25g. An organoleptic test was conducted to evaluate the color, taste, shape, compactness, aroma, and overall preference of each product variation. The results of the organoleptic test showed that the proportion of cassava flour and mung bean flour significantly affected the panelists' preferences. The 25g:25g proportion received the highest scores for color, taste, and compactness, while the 35g:15g proportion was preferred for aroma. The 30g:20g proportion demonstrated a good balance in all aspects but did not stand out in any specific category. Nutritional content analysis indicated that the snack bar with a combination of cassava flour and mung bean flour contained 57.81% carbohydrates, 11.82% protein, 6.05% fat, and 1.2% fiber. It can be concluded that the combination of cassava flour and mung bean flour in a 25g:25g proportion is the best formula favored by the panelists.